Method for preparing moisture-absorption antistatic polyester filament yarns from regenerated polyester fibers
By pretreating the regenerated polyester slices and adding antistatic agents and silicone during the melt spinning process, combined with the stretching and shaping step of high-temperature steam injection, the problem of insufficient hygroscopicity and antistatic properties of traditional regenerated polyester fiber products is solved, and the problem of insufficient hygroscopicity and antistatic properties of traditional regenerated polyester fiber products is achieved. Efficient hygroscopicity and antistatic properties are improved.
Patent Information
- Application Number
- CN202411638217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2025-02-21
Smart Images

Figure BDA0005137660730000071 
Figure BDA0005137660730000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of regenerated fiber filaments, and in particular to a method for preparing moisture-absorbing and antistatic polyester filaments from regenerated polyester fibers. Background Art
[0002] At present, with the increasing awareness of environmental protection, the use of recycled polyester fiber has gradually become a hot topic in the textile industry. However, traditional recycled polyester fiber products often face the problem of insufficient hygroscopicity and antistatic performance, which limits their wide application in the high-end clothing market. Although recycled polyester fiber resources are abundant, its own hydrophobicity leads to poor moisture absorption and breathability of the textiles made from it, and it is easy to generate static electricity, which reduces the wearing comfort and affects consumer acceptance.
[0003] Most of the existing improvement measures focus on surface treatment or blending modification, but these methods are often inefficient, complex in process, and costly, and the moisture absorption and antistatic effects are easily reduced after long-term washing. Summary of the invention
[0004] In order to improve the hygroscopicity and antistatic properties of polyester filaments, the present application provides a method for preparing hygroscopic and antistatic polyester filaments from regenerated polyester fibers.
[0005] The method for preparing hygroscopic and antistatic polyester filaments from regenerated polyester fibers provided in the present application adopts the following technical scheme: A method for preparing hygroscopic and antistatic polyester filaments from regenerated polyester fibers comprises the following steps: Pretreatment: preheating the recycled polyester chips at high temperature, and then immersing the recycled polyester chips in an anionic surfactant solution for pretreatment to obtain pretreated recycled polyester chips; Melt spinning: The pretreated recycled polyester chips, antistatic agent and silica gel are stirred and mixed evenly, and then melt-spinned to obtain recycled polyester fiber yarn; Stretching and shaping: The regenerated polyester fiber is stretched and shaped under the condition of high-temperature steam jet, and then cooled to obtain hygroscopic and antistatic polyester filament.
[0006] By adopting the above technical scheme, the recycled polyester chips are first preheated, and then pretreated with an anionic surfactant to improve its hydrophilicity. Then, during melt spinning, antistatic agent and silica gel are added. The antistatic agent improves the antistatic property of the fiber filaments. The silica gel improves the hygroscopicity of the obtained fiber filaments while improving the feel of the fiber filaments. Finally, the fiber filaments are stretched and shaped under high-temperature steam jet conditions and then cooled to promote the formation of micropores inside the fiber structure and enhance the moisture absorption capacity, thereby improving the hygroscopicity and antistatic properties of the final polyester filaments.
[0007] In a specific embodiment, the anionic surfactant in the anionic surfactant solution includes one or more of sodium stearate, sodium dodecylbenzene sulfonate, sodium lauryl sulfate, and sodium cocoyl isethionate.
[0008] In a specific embodiment, the pretreatment step is: preheating at 210-230° C. for 25-35 min, and then immersing the regenerated polyester chips in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated regenerated polyester chips.
[0009] In a specific embodiment, the mass concentration of the anionic surfactant in the anionic surfactant solution is 0.5-1.5 wt %.
[0010] By adopting the above technical solution, the preheating temperature and pretreatment time, as well as the mass concentration of the anionic surfactant are further limited, thereby improving the pretreatment effect on the recycled polyester chips, thereby improving the hygroscopicity of the polyester filaments.
[0011] In a specific embodiment, the preparation method of the antistatic agent comprises the following steps: γ-aminopropyltriethoxysilane, ethanol and water are stirred and mixed to obtain a spraying liquid; The conductive carbon black and carbon nanotubes are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, a spraying liquid is sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain an antistatic agent.
[0012] By adopting the above technical scheme, conductive carbon black and carbon nanotubes are modified by using γ-aminopropyltriethoxysilane, so that the dispersion performance of conductive carbon black and carbon nanotubes is improved, and conductive carbon black and carbon nanotubes have good conductivity, so that the obtained polyester filaments have good antistatic properties, and the γ-aminopropyltriethoxysilane on the surface of the antistatic agent can also improve the adhesion effect of conductive carbon black and carbon nanotubes on the polyester filaments.
[0013] In a specific embodiment, the weight ratio of the spraying liquid to the mixed material is 1:(13-14).
[0014] By adopting the above technical solution, the ratio of the spraying liquid to the mixed material is further limited, thereby improving the modification effect on the mixed material, and further improving the performance of the obtained antistatic agent.
[0015] In a specific embodiment, the melt spinning step is: stirring and mixing the pretreated regenerated polyester chips, antistatic agent, silica gel and nano-silver evenly, and then melt spinning to obtain regenerated polyester fiber filaments.
[0016] By adopting the above technical solution and adding nano-silver, polyester filament has excellent antibacterial and deodorizing effects, expanding its application range in the high-end market.
[0017] In a specific embodiment, in the melt spinning step, the weight ratio of the pretreated recycled polyester chips, antistatic agent, silica gel and nanosilver is 100:(1-3):(2-4):(0.2-0.4).
[0018] By adopting the above technical scheme, the ratio of pretreated recycled polyester chips, antistatic agent, silica gel and nano silver is further limited, thereby improving the hygroscopicity and antistatic properties of the obtained polyester filaments.
[0019] In a specific possible implementation method, the stretching and shaping step is: stretching and shaping the regenerated polyester fiber yarn under the condition of 110° C. steam spraying, and then naturally cooling for 30 seconds under the condition of relative humidity of 70% to obtain hygroscopic antistatic polyester filament.
[0020] By adopting the above technical solution, the temperature and humidity of stretching and shaping are further limited, thereby improving the stretching effect on the regenerated polyester fiber yarn.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, the recycled polyester chips are first preheated, and then pretreated with an anionic surfactant to improve its hydrophilicity. Then, during melt spinning, an antistatic agent and silica gel are added. The antistatic agent improves the antistatic property of the fiber filaments. The silica gel improves the hygroscopicity of the obtained fiber filaments and also improves the feel of the fiber filaments. Finally, the fibers are stretched and shaped under the condition of high-temperature steam jet, and then cooled to promote the formation of micropores inside the fiber structure and enhance the moisture absorption capacity, thereby improving the hygroscopicity and antistatic property of the polyester filaments finally obtained. 2. In the present application, γ-aminopropyltriethoxysilane is used to modify the conductive carbon black and carbon nanotubes, thereby improving the dispersion performance of the conductive carbon black and carbon nanotubes. The conductive carbon black and carbon nanotubes have good conductivity, so that the obtained polyester filaments have good antistatic properties. The γ-aminopropyltriethoxysilane on the surface of the antistatic agent can also improve the adhesion effect of the conductive carbon black and carbon nanotubes on the polyester filaments. 3. In this application, nano-silver is added during spinning, so that the polyester filament has excellent antibacterial and deodorizing effects, expanding its application range in the high-end market. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] All raw materials in the examples can be obtained from commercial sources. The anionic surfactant includes but is not limited to a mixture of one or more of sodium stearate, sodium dodecylbenzene sulfonate, sodium lauryl sulfate, and sodium cocoyl isethionate, and sodium dodecylbenzene sulfonate is preferred in the present application.
[0024] Preparation Example Preparation Example 1 Preparation Example 1 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Conductive carbon black and carbon nanotubes are stirred and mixed evenly to obtain a mixture. During the stirring process of the mixture, a spraying liquid is slowly sprayed into the mixture. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the conductive carbon black and the carbon nanotubes in the mixture is 1:1; and the weight ratio of the spraying liquid to the mixture is 1:12.5.
[0025] Preparation Example 2 Preparation Example 2 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Conductive carbon black and carbon nanotubes are stirred and mixed evenly to obtain a mixture. During the stirring process of the mixture, a spraying liquid is slowly sprayed into the mixture. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the conductive carbon black and the carbon nanotubes in the mixture is 1:1; and the weight ratio of the spraying liquid to the mixture is 1:13.
[0026] Preparation Example 3 Preparation Example 3 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Conductive carbon black and carbon nanotubes are stirred and mixed evenly to obtain a mixture. During the stirring of the mixture, a spraying liquid is slowly sprayed into the mixture. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the conductive carbon black and the carbon nanotubes in the mixture is 1:1; and the weight ratio of the spraying liquid to the mixture is 1:13.5.
[0027] Preparation Example 4 Preparation Example 4 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Conductive carbon black and carbon nanotubes are stirred and mixed evenly to obtain a mixture. During the stirring process of the mixture, a spraying liquid is slowly sprayed into the mixture. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the conductive carbon black and the carbon nanotubes in the mixture is 1:1; and the weight ratio of the spraying liquid to the mixture is 1:14.
[0028] Preparation Example 5 Preparation Example 5 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Conductive carbon black and carbon nanotubes are stirred and mixed evenly to obtain a mixture. During the stirring process of the mixture, a spraying liquid is slowly sprayed into the mixture. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the conductive carbon black and the carbon nanotubes in the mixture is 1:1; and the weight ratio of the spraying liquid to the mixture is 1:14.5.
[0029] Preparation Example 6 Preparation Example 6 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; The conductive carbon black is stirred and mixed evenly. During the stirring process, the spraying liquid is slowly sprayed into the conductive carbon black. After the spraying is completed, stirring is continued for 0.5 h, and then drying is carried out at 100° C. for 0.5 h to obtain an antistatic agent; wherein the weight ratio of the spraying liquid to the conductive carbon black is 1:13.5.
[0030] Preparation Example 7 Preparation Example 7 provides a method for preparing an antistatic agent, comprising the following steps: Stir and mix γ-aminopropyltriethoxysilane, ethanol and water to obtain a spraying liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; The carbon nanotubes were stirred and mixed evenly. During the stirring process, the spraying liquid was slowly sprayed into the carbon nanotubes. After the spraying was completed, stirring was continued for 0.5 h. Then, the mixture was dried at 100° C. for 0.5 h to obtain an antistatic agent. The weight ratio of the spraying liquid to the carbon nanotubes was 1:13.5. Example
[0031] Example 1 Embodiment 1 provides a method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber, comprising the following steps: Pretreatment: preheating the recycled polyester chips at 210° C. for 35 minutes, and then immersing them in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated recycled polyester chips; wherein the anionic surfactant solution is a mixture of anionic surfactant and water, and the anionic surfactant is sodium dodecylbenzene sulfonate with a mass concentration of 0.5wt%; Melt spinning: the pretreated regenerated polyester chips, the antistatic agent in Preparation Example 1, and the silica gel are stirred and mixed uniformly, and then melt-spinned to obtain regenerated polyester fiber yarn; wherein the weight ratio of the pretreated regenerated polyester chips, the antistatic agent, and the silica gel is 100:1:2; Stretching and shaping: The regenerated polyester fiber yarn is stretched and shaped under the condition of 110° C. steam jet, and then naturally cooled for 30 seconds under the condition of relative humidity of 70% to obtain hygroscopic antistatic polyester filament.
[0032] Example 2 The difference between Example 2 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 2, and the remaining steps are consistent with Example 1.
[0033] Example 3 The difference between Example 3 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 3, and the remaining steps are consistent with Example 1.
[0034] Example 4 The difference between Example 4 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 4, and the remaining steps are consistent with Example 1.
[0035] Example 5 The difference between Example 5 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 5, and the other steps are consistent with Example 1.
[0036] Example 6 The difference between Example 6 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 6, and the remaining steps are consistent with Example 1.
[0037] Example 7 The difference between Example 7 and Example 1 is that in the melt spinning step, the antistatic agent is the antistatic agent in Preparation Example 7, and the remaining steps are consistent with Example 1.
[0038] Example 8 The difference between Example 8 and Example 3 is that, pretreatment: the recycled polyester chips are first preheated at 220°C for 30 minutes, and then immersed in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated recycled polyester chips; wherein the anionic surfactant solution is a mixture of anionic surfactant and water, and the anionic surfactant is sodium dodecylbenzene sulfonate with a mass concentration of 1wt%, and the remaining steps are consistent with Example 3.
[0039] Example 9 The difference between Example 9 and Example 3 is that, pretreatment: the recycled polyester chips are first preheated at 230°C for 25 minutes, and then immersed in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated recycled polyester chips; wherein the anionic surfactant solution is a mixture of anionic surfactant and water, and the anionic surfactant is sodium dodecylbenzene sulfonate with a mass concentration of 1.5wt%, and the remaining steps are consistent with Example 3.
[0040] Example 10 The difference between Example 10 and Example 8 is that, in melt spinning, the pretreated regenerated polyester chips, the antistatic agent in Preparation Example 3, silica gel, and nano-silver are stirred and mixed evenly, and then melt-spun to obtain regenerated polyester fiber yarns; wherein the weight ratio of the pretreated regenerated polyester chips, the antistatic agent, silica gel, and nano-silver is 100:1:2:0.2, and the remaining steps are consistent with Example 8.
[0041] Embodiment 11 The difference between Example 11 and Example 10 is that, in melt spinning, the pretreated regenerated polyester chips, the antistatic agent in Preparation Example 3, silica gel, and nano-silver are stirred and mixed evenly, and then melt-spun to obtain regenerated polyester fiber yarns; wherein the weight ratio of the pretreated regenerated polyester chips, the antistatic agent, silica gel, and nano-silver is 100:2:3:0.3, and the remaining steps are consistent with Example 10.
[0042] Example 12 The difference between Example 12 and Example 10 is that, in melt spinning, the pretreated regenerated polyester chips, the antistatic agent in Preparation Example 3, silica gel, and nano-silver are stirred and mixed evenly, and then melt-spun to obtain regenerated polyester fiber yarns; wherein the weight ratio of the pretreated regenerated polyester chips, the antistatic agent, silica gel, and nano-silver is 100:3:4:0.4, and the remaining steps are consistent with Example 10.
[0043] Comparative Example Comparative Example 1 Comparative Example 1 provides a method for preparing polyester filament from regenerated polyester fiber, comprising the following steps: Melt spinning: The regenerated polyester chips, the antistatic agent in Preparation Example 1, and the silica gel are stirred and mixed evenly, and then melt-spinned to obtain regenerated polyester fiber yarns; wherein the weight ratio of the pretreated regenerated polyester chips, the antistatic agent, and the silica gel is 100:1:2; Stretching and shaping: The regenerated polyester fiber yarns are stretched and shaped under the condition of 110° C. steam spray, and then naturally cooled for 30 seconds under the condition of a relative humidity of 70% to obtain hygroscopic antistatic polyester filaments.
[0044] Comparative Example 2 Comparative Example 2 provides a method for preparing polyester filament from regenerated polyester fiber, comprising the following steps: Pretreatment: preheating the recycled polyester chips at 210° C. for 35 minutes, and then immersing them in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated recycled polyester chips; wherein the anionic surfactant solution is a mixture of anionic surfactant and water, and the anionic surfactant is sodium dodecylbenzene sulfonate with a mass concentration of 0.5wt%; Melt spinning: melt spinning the pretreated recycled polyester chips to obtain regenerated polyester fiber yarn; Stretching and shaping: The regenerated polyester fiber yarn is stretched and shaped under the condition of 110° C. steam jet, and then naturally cooled for 30 seconds under the condition of relative humidity of 70% to obtain hygroscopic antistatic polyester filament.
[0045] Performance test hygroscopicity: first wash the polyester filaments in each embodiment and comparative example twenty times and then dry them. Then control the temperature at 20±2°C and the relative humidity at 65±3%. Soak the polyester filaments in water for 3 hours. Then take out the filaments and drain them naturally. Finally, put them into a centrifuge and dehydrate them at 1500rpm for 10 minutes. Take out the filaments and quickly weigh them on an electronic balance and mark them as W1. Then, dry the filaments to constant weight in an electric blast drying oven at 105±3°C, quickly weigh them on an electronic balance and mark them as W0. Water retention rate = (W1-W0) / W0*100%. The higher the water retention rate, the better the hygroscopic performance of the filaments.
[0046] Antistatic property: The polyester filaments in each embodiment and comparative example were washed twenty times and then dried. The surface resistivity was tested according to GB / T12703.4-2010. The smaller the resistivity, the better the antistatic property of the filament.
[0047] Table 1 Performance test results of polyester filament In combination with Example 1 and Comparative Examples 1-2, the hygroscopicity and antistatic properties of the polyester filament in Example 1 are both good. It can be seen that using the preparation method in the present application, the regenerated polyester chips are first preheated, then pretreated with anionic surfactants to improve their hydrophilic properties, and then antistatic agents and silica gel are added during melt spinning. Finally, the fibers are stretched and shaped under high-temperature steam jet conditions and then cooled to promote the formation of micropores inside the fiber structure and enhance moisture absorption capacity, thereby improving the hygroscopicity and antistatic properties of the final polyester filaments.
[0048] Combined with Examples 1-5, the antistatic properties of the polyester filaments in Examples 2-4 are all good. It can be seen that when preparing the antistatic agent, the ratio of the spraying liquid to the mixed material is preferably 1: (13-14), and the antistatic agent obtained has better performance.
[0049] Combining Example 3, Example 6 and Example 7, the antistatic property of the polyester filament in Example 3 is the best. It can be seen that when preparing the antistatic agent, the raw material is preferably a mixture of conductive carbon black and carbon nanotubes, and the antistatic effect of the obtained antistatic agent is better.
[0050] Combining Example 3, Example 8 and Example 9, the hygroscopicity of the polyester filament in Example 8 is the best. It can be seen that when the recycled polyester chips are pretreated, the pretreatment conditions in Example 8 are the best, so the polyester filament has the best performance.
[0051] Combining Example 8 and Example 10, it can be seen that adding nano silver during melt spinning can improve the antibacterial and deodorizing properties of polyester, but has little effect on the hygroscopicity and antistatic properties.
[0052] In combination with Examples 10-12, the performance of the polyester filament in Example 11 is the best. It can be seen that during melt spinning, the ratio of the pretreated regenerated polyester chips, antistatic agent, silica gel, and nanosilver in Example 11 is optimal, thereby obtaining the best performance of the polyester filament.
[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber, characterized in that: The following steps are involved: Pretreatment: preheating the recycled polyester chips at high temperature, and then immersing the recycled polyester chips in an anionic surfactant solution for pretreatment to obtain pretreated recycled polyester chips; Melt spinning: The pretreated recycled polyester chips, antistatic agent and silica gel are stirred and mixed evenly, and then melt-spinned to obtain recycled polyester fiber yarn; Stretching and shaping: The regenerated polyester fiber is stretched and shaped under the condition of high-temperature steam jet, and then cooled to obtain hygroscopic and antistatic polyester filament.
2. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 1, characterized in that: The anionic surfactant in the anionic surfactant solution includes one or more of sodium stearate, sodium dodecylbenzene sulfonate, sodium lauryl sulfate, and sodium cocoyl isethionate.
3. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 2, characterized in that: The pretreatment step is: preheating at 210-230° C. for 25-35 minutes, and then immersing the regenerated polyester chips in an anionic surfactant solution for pretreatment for 1 hour to obtain pretreated regenerated polyester chips.
4. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 3, characterized in that: The mass concentration of the anionic surfactant in the anionic surfactant solution is 0.5-1.5wt%.
5. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 1, characterized in that: The preparation method of the antistatic agent comprises the following steps: γ-aminopropyltriethoxysilane, ethanol and water are stirred and mixed to obtain a spraying liquid; The conductive carbon black and carbon nanotubes are stirred and mixed uniformly to obtain a mixture. During the stirring of the mixture, a spraying liquid is sprayed into the mixture. After the spraying is completed, the mixture is continuously stirred and dried to obtain an antistatic agent.
6. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 5, characterized in that: The weight ratio of the spraying liquid to the mixed material is 1:(13-14).
7. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 1, characterized in that: The melt spinning step comprises: mixing the pretreated regenerated polyester chips, antistatic agent, silica gel and nano silver uniformly, and then melt spinning to obtain regenerated polyester fiber yarns.
8. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 7, characterized in that: In the melt spinning step, the weight ratio of the pretreated recycled polyester chips, the antistatic agent, the silica gel and the nano-silver is 100:(1-3):(2-4):(0.2-0.4).
9. The method for preparing hygroscopic antistatic polyester filament from regenerated polyester fiber according to claim 1, characterized in that: The stretching and shaping step comprises: stretching and shaping the regenerated polyester fiber yarn under the condition of 110° C. steam spraying, and then naturally cooling for 30 seconds under the condition of 70% relative humidity to obtain hygroscopic antistatic polyester filament.